2019
DOI: 10.3389/fmats.2019.00275
|View full text |Cite
|
Sign up to set email alerts
|

Soil Biodegradation of Unidirectional Polyhydroxybutyrate-Co-Valerate (PHBV) Biocomposites Toughened With Polybutylene-Adipate-Co-Terephthalate (PBAT) and Epoxidized Natural Rubber (ENR)

Abstract: The detrimental impact of discarded plastics on the environment has become of increasing concern and this has led to the development of environmentally friendly "green" polymers. PHBV is one such green polymer that offers biodegradability and renewability, however its mechanical performance is quite limited. This can be improved by reinforcement with natural fibers to form green composites, which offer better mechanical properties while retaining biodegradability. There are, however, few studies examining the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Some success has been found in PHBV/PBAT/flax composites where soil degradation rate of PHBV and flax in the composite was enhanced with PBAT addition, however this was attributed to phase separation that improved microbial ingress into the samples. 211 In higher temperature environments (∼58°C) such as controlled composting and anaerobic digestion, the biodegradation of PLA is common, and it is expected that there would be benefits of incorporating PHAs into PLA to improve the compostability. However, PLA/PHBV 70/30 blends have shown no biodegradation improvement compared to PLA and PHBV alone (all 90-92% biodegradation in 200 days) under ASTM D5338-15, 175 or have even a reduced biodegradation rate in compost, 212 and under anaerobic digestion.…”
Section: Chemical Additives and Blending Effect On Pha Biodegradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some success has been found in PHBV/PBAT/flax composites where soil degradation rate of PHBV and flax in the composite was enhanced with PBAT addition, however this was attributed to phase separation that improved microbial ingress into the samples. 211 In higher temperature environments (∼58°C) such as controlled composting and anaerobic digestion, the biodegradation of PLA is common, and it is expected that there would be benefits of incorporating PHAs into PLA to improve the compostability. However, PLA/PHBV 70/30 blends have shown no biodegradation improvement compared to PLA and PHBV alone (all 90-92% biodegradation in 200 days) under ASTM D5338-15, 175 or have even a reduced biodegradation rate in compost, 212 and under anaerobic digestion.…”
Section: Chemical Additives and Blending Effect On Pha Biodegradationmentioning
confidence: 99%
“…For example, PHBV (8% HV) powder tested in sand (dry silica with low organic material) achieved 80% biodegradation after 600 days, 176 which is significantly longer than most soil biodegradation tests. Zaidi et al 211 reported no degradation of PHBV (3% HV) in botany sand in a natural environment within 110 days. Sand has relatively poor moisture holding capacity, substantiating these slow biodegradation rates that take months to years for any evidence and by mixing in organic soil and farm soil into sand, the biodegradation rate of PHAs is not seen to improve 113 (Table 1, entry 12).…”
Section: Green Chemistry Critical Reviewmentioning
confidence: 99%
“…The reduction of mechanical performances could be associated with the fast T-PHBV biodegradation kinetics, as widely reported in the literature and confirmed by the quick structural collapse of T-PHBV samples after only 14 days [ 25 , 26 ]. Besides, T-PHBV biodegradation was supported by the peculiar soil substrate composition and microclimate generated inside the garden soil; the synergistic action of organic compost, acid pH and constant RH of 50 % could induce and hasten the biodegradation process by means of both microorganism attack (as SEM micrographs confirmed) and hydrolytic action on the polymer backbone (as demonstrated by GPC analysis) [ [27] , [28] , [29] ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Although numerous works that reported on recovery by recycling, biodegradation test, or even toxicity (such as ecotoxicity with plants) of biodegradable polymers are observed [1,4,[10][11][12], the composites or nanocomposites produced with these polymers have been very little considered [13,14]. Commonly, biodegradable polymers are processed with other polymers (polymer blends) or reinforced with filler or nanofiller, generating composites or nanocomposites with enhanced properties [2,[15][16][17][18][19][20][21][22][23][24][25]. Few studies address the effect of the addition of the nanofiller on the polymer biodegradation property [4,21,[26][27][28][29][30][31][32], and even fewer studies have investigated what happens to the nanofillers after polymer biodegradation [26].…”
mentioning
confidence: 99%
“…Commonly, biodegradable polymers are processed with other polymers (polymer blends) or reinforced with filler or nanofiller, generating composites or nanocomposites with enhanced properties [2,[15][16][17][18][19][20][21][22][23][24][25]. Few studies address the effect of the addition of the nanofiller on the polymer biodegradation property [4,21,[26][27][28][29][30][31][32], and even fewer studies have investigated what happens to the nanofillers after polymer biodegradation [26]. Since most parts of the inserted nanofillers are not biodegradable, studies about their destination should be considered in the research of nanocomposites.…”
mentioning
confidence: 99%